2009
DOI: 10.1007/s11095-009-9926-y
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid, an Active Constituent of Grape Seed Extract, Exhibits Anti-proliferative, Pro-apoptotic and Anti-tumorigenic Effects Against Prostate Carcinoma Xenograft Growth in Nude Mice

Abstract: Purpose-Gallic acid, a natural agent present wide-range of fruits and vegetables, has been of potential interest as anti-cancer agent; herein, we evaluated its efficacy in androgen-independent DU145 and androgen-dependent-22Rv1 human prostate cancer (PCa) cells Materials and Methods-Cell viability was determined by MTT and apoptosis by Annexin V-PI assays. In vivo anti-cancer efficacy was assessed by DU145 and 22Rv1 xenograft growth in nude mice given normal drinking water or one supplemented with 0.3% or 1% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(149 citation statements)
references
References 32 publications
6
140
1
2
Order By: Relevance
“…Several previous data have demonstrated that GT has pro-apoptotic and antiinflammatory effects (Kaur et al 2009). Although many results have shown that GT induces apoptosis in A549 cells, the underlying molecular mechanisms are yet to be properly characterized.…”
Section: Discussionmentioning
confidence: 97%
“…Several previous data have demonstrated that GT has pro-apoptotic and antiinflammatory effects (Kaur et al 2009). Although many results have shown that GT induces apoptosis in A549 cells, the underlying molecular mechanisms are yet to be properly characterized.…”
Section: Discussionmentioning
confidence: 97%
“…Gallic acid (3,4,5-trihydroxybenzoic acid, GA), a naturally occurring plant phenol, is abundant in natural plants (15)(16)(17)(18)(19) and it has been reported to have anti-bacterial (20), anti-viral (21), anti-inflammatory (16), antioxidant (22) and antitumor functions in many human cancer cell lines (21)(22)(23). Although GA has been shown to inhibit the growth of prostate cancer cells, there is no available information addressing GA-inhibited migration and invasion of prostate cancer cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis was determined by staining cells with Annexin V-fluorescein isothiocyanate (FITC, PharMingen, San Diego, CA; Ex/Em = 488 nm/519 nm) and propidium iodide (PI; Sigma-Aldrich; Ex/Em = 488 nm/617 nm). In brief, 1x10 6 cells in 60 mm culture dish (Nunc) were incubated with the indicated amounts of GA with or without p38 inhibitor for 24 h. Cells were washed twice with cold PBS and then resuspended in 500 μl of binding buffer (10 mM HEPES/NaOH pH 7.4, 140 mM NaCl, 2.5 mM CaCl 2 ) at a concentration of 1x10 6 cells/ml. Five microliters of Annexin V-FITC and PI (1 μg/ml) were then added to these cells, which were analyzed with a FACStar flow cytometer (Becton-Dickinson).…”
Section: Methodsmentioning
confidence: 99%
“…The major interest in GA is related to its antitumoral activity. Anticancer activity of GA has been reported in various cancer cells, such as prostate cancer (6), lung cancer (7,8), gastric, colon, breast, cervical and esophageal cancer (9). Apoptosis induced by GA is associated with oxidative stresses derived from reactive oxygen species (ROS), mitochondrial dysfunction and an increase in intracellular Ca 2+ level (10,11).…”
Section: Introductionmentioning
confidence: 99%